Ileal atresia with intraluminal Meckel's diverticulum - Ibrahim Ali Ibrahim; Ahmed Kamel Ali Mohamed (Elsevier, 2023)
Background: Jejuno-ileal atresia is a major cause of neonatal intestinal obstruction with a prevalence of 1.8 per 10 000 live births. It is thought to arise from intrauterine vascular accident. Meckel's diverticulum is the most common congenital anomaly of the gastrointestinal tract and associated with incomplete obliteration of the vitelline duct. In this study we present very rare two cases with ileal atresia type IIIa and intraluminal Meckel's diverticulum which are considered first cases of literature. Case presentation: Case 1: First patient was a full-term male neonate born to a 26-year-old mother via caesarean section. He was presented with repeated bilious vomiting and failure to pass meconium since birth. On physical examination patient had moderate diffuse abdominal distension with stepladder view. Plain erect abdominal radiograph showed multiple air fluid level with no gas under diaphragm. Pelviabdominal ultrasound showed signs of intestinal obstruction. Gastrograffin enema revealed small caliber through whole length of the colon. After failure of conservation for 24 hours, we prepare him for urgent exploration. Intraoperatively we found type IIIa ileal atresia 50 cm from ileocecal junction with inverted Meckel's diverticulum in distal end. resection of atretic part containing Meckel's diverticulum and end to end hand sewn anastomosis was done. Patient started oral feeding on 3rd day and discharged with good general condition on 7th day postoperatively.Case 2: A full-term 2-day old female neonate was born to a 20-year-old mother via vaginal delivery at our hospital and presented to our unit complaining of failure of passage of meconium and repeated bilious vomiting since birth. Plain erect abdominal radiograph showed multiple air fluid level with no gas under diaphragm. Gastrograffin enema revealed small caliber through whole length of the colon. After correction of his general condition, we prepare him for urgent exploration. We found type IIIa ileal atresia 65 cm from ileocecal junction with inverted Meckel's diverticulum in distal end. resection of atretic part containing Meckel's diverticulum and end to end hand sewn ileo-ileal anastomosis was done. Patient started oral feeding on 2nd day and discharged with good general condition on 9th day postoperatively. Conclusions: We report very rare two cases of ileal atresia with intraluminal Meckel's diverticulum which is considered first cases of literature. In ileal atresia, Meckel's diverticulum must be considered and if it is present, it is advised to be resected to prevent its life-threatening complications later.